The effects of authentic personal branding on academic librarians’ professional image in Malaysia / Rosnani Ahmad - Ahmad, Rosnani (2019)
Authentic personal branding emerges from academic librarians’ true characters, values, strengths, uniqueness, and genius that in the end are about sustainability, authenticity, consistency, and the memorable personal brand. This quantitative study aims to identify the dimension, factors and examine the effects of authentic personal branding (APB) on academic librarians’ professional image in Malaysia. The effects of APB focuses on the academic librarians’ (a) reputation in a university, (b) responsibilities to library users and library services, and (c) their relationship with library users. The study covers 344 academic librarians specifically from 20 Public Institution of Higher Education (PIHE) in Malaysia. The questionnaires were distributed to the respondents according to purposive sampling as the main intention to identify all academic librarians in the selected universities. In details it applies the maximum variation sampling techniques in order to capture a wide range of perspectives related to the effects of authentic personal branding on academic librarians’ professional image. The results were analysed using SPSS version 23 and Smart PLS 3.0 and involved combination of two types of study that are descriptive and causal or correlation. The findings found that authentic personal branding play a very significant role in effecting the academic librarians’ professional image in Malaysia especially dealing with the personal ambition, personal brand and personal balanced scorecard on regards to their reputation in the University. Whereas, determinant for the responsibilities of the librarians to the library users and relationship with library users, only the personal balanced scorecard constructs significant to the study. These findings highlight the important role of having the authentic personal branding approach and strategies which at the end result a significant value to the academic librarians’ professional image. Further studies are recommended to examine the reason behind the insignificant relationship in this study besides using a mixed method approach or qualitative research. This study helps in providing ideas to Malaysian librarians in creating a new tune of modern day needs for the librarianship profession and upgrading their personal professionalism by adapting the relevance criteria for effective authentic personal branding as the essence of wealth generation, to serve the community with the best talent skills and quality services.